2018
DOI: 10.1002/bies.201800031
|View full text |Cite
|
Sign up to set email alerts
|

Synapse Pruning: Mitochondrial ROS with Their Hands on the Shears

Abstract: No overarching hypotheses tie the basic mechanisms of mitochondrial reactive oxygen species (ROS) production to activity dependent synapse pruning-a fundamental biological process in health and disease. Neuronal activity divergently regulates mitochondrial ROS: activity decreases whereas inactivity increases their production, respectively. Placing mitochondrial ROS as innate synaptic activity sentinels informs the novel hypothesis that: (1) at an inactive synapse, increased mitochondrial ROS production initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 120 publications
0
13
0
Order By: Relevance
“…Local availability of mitochondrial mass is critical for generating and sustaining dendritic arbors, and disruption of mitochondrial distribution in mature neurons is associated with structural alterations in neurons (Kuzawa et al, 2014;Ló pez-Domé nech et al, 2016;Spillane et al, 2013). Loss of interneurons (Lax et al, 2016) and synapses and dendritic atrophy (in number and size) in specific brain areas, such as various cortical areas, the cerebellum, thalamus, and basal ganglia (Betts et al, 2006;Briston and Hicks, 2018;Chen et al, 2017;Cobley, 2018;Quintana et al, 2010;Turnbull et al, 2010) have also been reported in individuals with mitochondrial dysfunction. We found a reduced number of primary dendrites and dendritic nodes, decreased total and mean dendritic length, as well as a reduced surface covered by the dendritic network.…”
Section: Discussionmentioning
confidence: 99%
“…Local availability of mitochondrial mass is critical for generating and sustaining dendritic arbors, and disruption of mitochondrial distribution in mature neurons is associated with structural alterations in neurons (Kuzawa et al, 2014;Ló pez-Domé nech et al, 2016;Spillane et al, 2013). Loss of interneurons (Lax et al, 2016) and synapses and dendritic atrophy (in number and size) in specific brain areas, such as various cortical areas, the cerebellum, thalamus, and basal ganglia (Betts et al, 2006;Briston and Hicks, 2018;Chen et al, 2017;Cobley, 2018;Quintana et al, 2010;Turnbull et al, 2010) have also been reported in individuals with mitochondrial dysfunction. We found a reduced number of primary dendrites and dendritic nodes, decreased total and mean dendritic length, as well as a reduced surface covered by the dendritic network.…”
Section: Discussionmentioning
confidence: 99%
“…The local availability of mitochondrial mass is critical for generating and sustaining dendritic arbors, and disruption of mitochondrial distribution in mature neurons is associated with structural alterations in the neurons (López-Doménech et al, 2016;Spillane et al, 2013;Kuzawa et al, 2014). Loss of interneurons , synapses and dendritic atrophy (both in number and size) in specific brain areas, such as various cortical areas, cerebellum, thalamus and basal ganglia (Cobley, 2018;Chen et al, 2017;Quintana et al, 2010;Betts et al, 2006;Turnbull et al, 2010;Briston and Hicks, 2018) have also been reported in individuals with mitochondrial dysfunction. We found a reduced number of primary dendrites and dendritic nodes, decreased total-and mean dendritic length, as well as reduced surface, covered by the dendritic network.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, our results underscore the impact of mitochondria on cortical networks and cognition. Mitochondria not only play essential roles in cell function, but their bioenergetics are crucial for proper neuronal development (Cobley, 2018), and even acute dysfunction impairs learning and memory (Mancini and Horvath, 2017). Here we illustrate how CypD activity can drive mitochondrial dysfunction in PVI and show that CypD may be a potential therapeutic target in protecting cognitive function in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%